Clinical and prognostic significance of serum levels of von Willebrand factor and ADAMTS-13 antigens in AL amyloidosis - Kastritis, E.; Papassotiriou, I; Terpos, E.; Roussou, M.; Gavriatopoulou, M.; Komitopoulou, A.; Skevaki, C.; Eleutherakis-Papaiakovou, E.; Pamboucas, C.; Psimenou, E.; Manios, E.; Giannouli, S.; et al. (Blood, 2016)
Cardiac dysfunction determines prognosis in amyloid light-chain (AL) amyloidosis. The heart is the central organ of the vascular system in which endothelium function is critical for the circulatory homeostasis, but there are limited data on endothelial function in AL amyloidosis. von Willebrand factor (VWF) has been considered as a marker of endothelial activation and dysfunction, whereas a disintegrin and metalloproteinase with thrombospondin type-1 repeats 13 (ADAMTS-13) cleaves VWF multimers, but both have been associated with prognosis in cardiovascular disease. We measured the serum levels of VWF (VWF:Ag) and ADAMTS-13 antigens in 111 newly diagnosed patients with AL amyloidosis. The levels of VWF:Ag were significantly higher than in healthy controls; 76% of patients with AL had VWF:Ag levels higher than the upper levels of controls. There was no significant association of VWF:Ag levels with patterns of organ involvement, free light-chain levels, the levels of cardiac biomarkers, or renal dysfunction but correlated with low systolic blood pressure. VWF:Ag levels ≥230.0 U/dL were associated with higher probability of early death and poor survival independently of cardiac biomarkers and low systolic blood pressure (SBP). Moreover, among patients with Mayo stage III or stage IIIB (that is stage III with N-terminal pro-brain natriuretic peptide [NTproBNP] >8500 pg/mL) disease, VWF:Ag identified subgroups of patients with very poor outcome. Low ADAMTS-13 levels correlated with high levels of NTproBNP but had no independent prognostic significance. In conclusion, high VWF:Ag levels, probably representing endothelial dysfunction, are associated with prognosis in patients with AL amyloidosis, independently of other features of the disease or cardiac biomarkers. © 2016 by The American Society of Hematology.